THE ROLE OF WOMEN IN THE DEVELOPMENT OF THE EDUCATION SYSTEM IN UZBEKISTAN (1991-2023) - Shahnoza Elboyeva (Bright Mind Publishing, 2025)
This article analyzes the role and significance of women in Uzbekistan's education system since the country's independence. Since 1991, the government of Uzbekistan has implemented a series of reforms aimed at ensuring gender equality, expanding educational opportunities for women, and enhancing their participation in society. The article discusses the privileges provided to women in education, their achievements in the development of Uzbekistan’s education system, and the impact of these processes on the country’s sustainable development.
Keywords: Uzbekistan, education system, women, gender equality, master's degree, reforms, educational privileges, science, achievements, role of women, Uzbekistan’s independence.